Resolving a dusty, star-forming SHiZELS galaxy at z = 2.2 with HST, ALMA, and SINFONI on kiloparsec scales. Issue 2 (19th February 2021) - Cochrane, R K; Best, P N; Smail, I; Ibar, E; Cheng, C; Swinbank, A M; Molina, J; Sobral, D; Dudzevičiūtė, U
ABSTRACT: We present ∼0.15 arcsec spatial resolution imaging of SHiZELS-14, a massive (M_*10^11 M_ ), dusty, star-forming galaxy at z = 2.24. Our rest-frame 1 kpc -scale, matched-resolution data comprise four different widely used tracers of star formation: the H α emission line (from SINFONI/VLT), rest-frame UV continuum (from HST F606W imaging), the rest-frame far-infrared (from ALMA), and the radio continuum (from JVLA). Although originally identified by its modest H α emission line flux, SHiZELS-14 appears to be a vigorously star-forming (SFR1000 M_ yr^-1 ) example of a submillimetre galaxy, probably undergoing a merger. SHiZELS-14 displays a compact, dusty central starburst, as well as extended emission in H α and the rest-frame optical and FIR. The UV emission is spatially offset from the peak of the dust continuum emission, and appears to trace holes in the dust distribution. We find that the dust attenuation varies across the spatial extent of the galaxy, reaching a peak of at least A H α ∼ 5 in the most dusty regions, although the extinction in the central starburst is likely to be much higher. Global star-formation rates inferred using standard calibrations for the different tracers vary from 10\!-\!1000 M_ yr^-1, and are particularly discrepant in the galaxy's dusty centre. This galaxy highlights the biased view of the evolution of star-forming galaxies provided by shorter wavelength data.